PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN KONSUMEN KALIBAN HOTEL - VUSPITA .; HERYENZUS . (JURNAL ILMIAH KOHESI, 2020)
The tourism industry is growing, it needs help from the hotel industry to take part in providing tourism trips. The hotelprovides, services, food, drinks, other facilities provided. Likert scale, and researchers used a questionnaire. The methodused in this study was multiple linear regression. The population in the study was visitors of the Kaliban hotel in the July-December 2020 period looking for 1,203. Some of the research used in the discussion of this thesis uses Slovin researchwhich obtained 300 respondents. The t test results of the quality variables are related to positive partial which has a positiveinfluence on customer satisfaction can be seen from the test with the tcount obtained at 9,750 ≥ t table 1,968 and for thesignificance value obtained 0,000 ≤ 0.05. Variable quality of service and multan facilities have a positive and significantincome to customer satisfaction, as evidenced by the results of the f test that is processed with a calculation value of453,415 ≥ ftable 2.63 and the value of sig obtained 0,000 ≤ 0.05 can be used as a variable of service quality and positivefacilitation and significant for customer satisfaction.